2007
DOI: 10.1128/jvi.01311-06
|View full text |Cite
|
Sign up to set email alerts
|

An RNA-Binding Protein, hnRNP A1, and a Scaffold Protein, Septin 6, Facilitate Hepatitis C Virus Replication

Abstract: Hepatitis C virus (HCV) is a positive-sense single-stranded RNA virus. NS5b is an RNA-dependent RNA polymerase that polymerizes the newly synthesized RNA. HCV likely uses host proteins for its replication, similar to other RNA viruses. To identify the cellular factors involved in HCV replication, we searched for cellular proteins that interact with the NS5b protein. HnRNP A1 and septin 6 proteins were identified by coimmunoprecipitation and yeast two-hybrid screening, respectively. Interestingly, septin 6 prot… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
83
0

Year Published

2009
2009
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 90 publications
(85 citation statements)
references
References 76 publications
2
83
0
Order By: Relevance
“…A previous report showed that the arenavirus Pichinde virus causes a transient cytoplasmic translocation of hnRNP A1 (Bowick et al, 2009). Here, we demonstrated that acute JUNV infection induces the cytoplasmic accumulation of hnRNP A1 in most infected cells but, in accordance with previous results obtained for hepatitis C virus-infected cells (Kim et al, 2007), some infected cells exhibited a nuclear hnRNP A1 pattern of distribution. The m.o.i.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…A previous report showed that the arenavirus Pichinde virus causes a transient cytoplasmic translocation of hnRNP A1 (Bowick et al, 2009). Here, we demonstrated that acute JUNV infection induces the cytoplasmic accumulation of hnRNP A1 in most infected cells but, in accordance with previous results obtained for hepatitis C virus-infected cells (Kim et al, 2007), some infected cells exhibited a nuclear hnRNP A1 pattern of distribution. The m.o.i.…”
Section: Discussionsupporting
confidence: 92%
“…Since all hnRNP A/B proteins are structurally similar and are particularly homologous in their RNAbinding domains it would not be surprising if they replaced each other in their functions. 2007; Cammas et al, 2007;Kim et al, 2007;Lin et al, 2008Lin et al, , 2009Gui et al, 2010). A previous report showed that the arenavirus Pichinde virus causes a transient cytoplasmic translocation of hnRNP A1 (Bowick et al, 2009).…”
Section: Discussionmentioning
confidence: 99%
“…Our study using both HCV replicon and JFH1 infectious cell culture systems clearly demonstrates that depletion of HuR leads to a significant reduction in the HCV RNA and protein levels. HuR has been shown to stimulate IRES-driven translation of HCV RNA (25). Interestingly, in our assay it appears that HuR plays a more dominant role in the replication step of the viral life cycle than in translation.…”
Section: Discussionmentioning
confidence: 61%
“…La and PCBP2 proteins have been shown to interact with both of the UTRs and link the 5= and 3= ends of the viral genome, facilitating replication (22,23). Other independent studies on RNA binding proteins like hn-RNPD, hnRNPA1, HuR, Unr, hnRNPU, etc., have indicated that they interact with the viral RNA (24)(25)(26)(27). However, the molecular basis of regulation of viral replication by these RBPs remains a mystery.…”
mentioning
confidence: 99%
“…Dysfunction of the mammalian septin family has been identified in diverse pathologies, including neoplasia (Montagna et al, 2003), neurodegenerative conditions (Kinoshita et al, 1998) and infections (Kim et al, 2007). However, the function of septins in the kidney in vivo has not been studied; such analysis is required to test the relevance of the functions of septins in ciliogenesis and cilia structure that have been identified in epithelial cells in tissue culture.…”
Section: Introductionmentioning
confidence: 99%